2020
DOI: 10.1002/nag.3049
|View full text |Cite
|
Sign up to set email alerts
|

Error‐controlled implicit time integration of elasto‐visco‐plastic constitutive models for rock salt

Abstract: The mechanical behavior of rock salt is rate-dependent at different time scales. Using caverns in rock salt formations for renewable energy storage implies that the underground structures are subjected to both short-term and long-term loads, increasing robustness and flexibility requirements for numerical simulators used to assess the safety of such structures. So far, explicit time integration with model-specific heuristics for time-step size determination dominate in application studies. In this paper, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…_ γ c can be thought of as a viscoplastic strain rate _ ϵ vp , similar to the viscoplastic strain rate used in other models. [39][40][41] For example, Duvaut and Lions suggested that _ ϵ vp should be a function of local stress, local stiffness, and the relaxation time. 42 In Perzyna's model, _ ϵ vp is proportional to the derivative of yield surface with respect to local stress.…”
Section: Homogenization Scheme: From Local Sliding To Rate-dependenmentioning
confidence: 99%
“…_ γ c can be thought of as a viscoplastic strain rate _ ϵ vp , similar to the viscoplastic strain rate used in other models. [39][40][41] For example, Duvaut and Lions suggested that _ ϵ vp should be a function of local stress, local stiffness, and the relaxation time. 42 In Perzyna's model, _ ϵ vp is proportional to the derivative of yield surface with respect to local stress.…”
Section: Homogenization Scheme: From Local Sliding To Rate-dependenmentioning
confidence: 99%
“…An elastic-viscoplastic model was proposed by Yin and Graham [ 215 ] in terms of the flow surface and the modified Cam-clay model. Recently, new visco-plastic constitutive models have been used for creep analysis in soft rocks or soils that some of them mentioned in the following [ [216] , [217] , [218] ].…”
Section: Classifying the Constitutive Relationsmentioning
confidence: 99%
“…On the other hand, implementing the models into the finite element method (FEM) commercial software is significant for applying in the practical engineering. Diverse algorithms for integration of complex and highly nonlinear constitutive models have been developed, which can be generally divided into the following three categories, implicit algorithms, [31][32][33] explicit algorithms, [34][35][36] and semi-implicit algorithms. 37,38 The implicit integrations update the unknown values of the variables at current loading step through an iterative process.…”
Section: Introductionmentioning
confidence: 99%